Characterization of novel cellulose nanofibril and phenolic acid-based active and hydrophobic packaging films. (16th April 2022) - LakshmiBalasubramaniam, SuriyaPrakaash; Howell, Caitlin; Tajvidi, Mehdi; Skonberg, Denise
Highlights: Phenolic acid esterification yields antioxidant Cellulose Nanofibril (CNF) films. Esterified CNF films have active functionality and extend shelf life of fatty foods. Hydrophobicity of CNF films improved after phenolic acid esterification. Esterification does not negatively affect mechanical properties of CNF films. Abstract: Cellulose nanofibril (CNF) is a natural biodegradable biopolymer with excellent mechanical and barrier properties. However, it is susceptible to moisture-induced deterioration of its properties. Attachment of phenolic acids can improve its hydrophobicity and provide additional active functionalities such as antioxidant properties. In this study, CNF films were esterified to vanillic and syringic acid through two different reaction mechanisms. The films were investigated for evidence of modification, hydrophobicity, mechanical properties, crystallinity, thermal stability, and antioxidant properties. Results indicate that esterification with vanillic and syringic acids imparted antioxidant activity to CNF films, with a significantly higher ABTS +· scavenging activity (76 ± 18%) when compared to control CNF films (30 ± 6%). Similarly, esterification of phenolic acids significantly improved the hydrophobicity of the films with a water contact angle of 94 ± 3° when compared to control CNF films (46 ± 5°). Covalent attachment of phenolic acids can improve hydrophobicity while providing additional functionality to CNF important for food packaging applications.